Trends and Directions of TPACK Research in Education: A Thematic Analysis of 26 Scopus-Indexed Articles from 2021–2025 - Neldarisasmita Neldarisasmita; Hardina Ullfa; Isni Rahma Apriyanti; Rayandra Asyhar; Ilham Falani (Journal of Science and Science Education, 2026)
This study aims to analyze the development of themes and focus of studies in recent research using the Technological Pedagogical Content Knowledge (TPACK) framework in the field of education. A total of 600 initial documents with the keyword "TPACKFramework" were retrieved from the Scopus database, then filtered based on the year of publication (2021–2025), document type (article), language (English), open access, and content relevance. A further filtering process was carried out through the rayyan.id platform by removing review-type articles and selecting only articles that explicitly discuss TPACK in the context of education. The final results of 26 articles were further analyzed using a thematic analysis approach to identify key patterns and emerging scientific trends. Data visualization was performed using VOSviewer software to map relationships between keywords, theme clusters, and temporal dynamics. The results show that TPACK has developed into an operational framework in teacher training, STEM education, and the integration of digital learning at various levels of education. Furthermore, the emergence of derivative approaches such as DPACK and AI-TPACK demonstrates the evolution of concepts in response to the increasingly complex needs of technology-based learning. Studies also show that mastery of TPACK has a direct impact on improving critical thinking skills, creativity, and innovation in both teachers and students. This study concludes that the direction of TPACK research is shifting from emergency pandemic responses to more adaptive, technology-based long-term learning designs